Equal pay film, 1951 (1951)
1951 1945-1960 "Equal pay film, 1951" [EP0047a], 1951 Jill Craigie made the equal pay documentary film To be a woman in 1951. It was distributed through Regent Films and the Equal Pay Campaign Committee. This article is from the September 1951 issue of Taxes, the journal of the Inland Revenue Staff Federation.